Penerapan Senam Kaki Pada Penderita Diabetes Mellitus dalam Upaya Pencegahan Komplikasi Diabetes pada Kaki (Diabetic Foot) - Syah, Afni Yan; Pertiwi, Eri Riana; Delianti, Nosi; Juliana, Juliana (Sekolah Tinggi Ilmu Kesehatan KESDAM IX/Udayana, 2023)
Background: Diabetes Mellitus (DM) is a disease that is increasing every year in countries around the world. Reports from various regions in Indonesia show that the incidence and complications of DM are widespread, making it a national problem that requires more attention. A frequently encountered complication of DM is diabetic foot, which can manifest as ulcers, infection and gangrene. Actions to treat diabetic foot include preventive measures which include foot care education, diabetic shoes and foot exercises. Foot exercises are exercises carried out by DM sufferers and non-sufferers to prevent injuries and help improve blood circulation in the legs. Apart from their role in providing health education, nurses as members of the medical team can also play a role in teaching foot exercises so that DM patients are able to do foot exercises independently. Objective: To increase the knowledge and skills of DM sufferers by implementing foot exercises in an effort to prevent diabetes complications in the feet (diabetic foot). Method: Foot exercise activities are carried out on DM sufferers who do not have wounds on the feet. The methods used were lectures, questions and answers, and direct demonstrations using newspapers. Results: The results of the activities obtained were an increase in knowledge before and after providing counseling and demonstrations of foot exercises for DM sufferers. Conclusion: After carrying out this community service, the community's ability to do foot exercises has increased and can be done independently, so it is hoped that this can prevent complications in DM sufferers.